The relationship between application of learning strategies and self-efficacy among ESL learners in the Faculty of Mass Communication,Universiti Teknologi MARA : a case study / Muhammad Irfan Mokhtar - Mokhtar, Muhammad Irfan (2013)
Proficiency in the second language lesson is very much determined by language learning strategies. Strategies of language learning are defined as strategies that contribute to the development of the language system which the learner constructs and affects learning directly (Rubin, 1987). There are six major categories of language learning strategies as developed by Oxford (1990). They are memory strategies,cognitive strategies, compensation strategies, metacognitive strategies, affective strategies and social strategies. This study was conducted to investigate the interrelationships among language learning strategy used, and self-efficacy that lead to proficiency in the second language. The respondents were a hundred and nine students from the Faculty of Mass Communication of Universiti Teknologi MARA (UiTM).The students' use of language learning strategies was measured through a fifty-item questionnaire that was an adaptation of Oxford's (1990) Strategy Inventory for Language Learning (SILL). Their self-efficacy was also measured through a twenty eight-item questionnaire developed by Gahungu (2007) in which they expressed their levels of certainty that they could perform learning tasks at desired levels of proficiency. The results of the study revealed the existence of positive and significant relationships among the two variables measured. Recommendations for further study include other determining factors that would contribute to further understand on what and how those factors affect learners' preferences and application of learning strategies, thus explore on its relationship with self-efficacy.